Association of secondary traits with yield in maize F 1 's - Nardino,Maicon (2016)
ABSTRACT: The objective was to identify phenotypic and genotypic associations, and cause-and-effect relations of secondary components on primary components to establish criteria in the indirect selection process for maize. Partial diallel crosses were conducted in Clevelândia. F1's were evaluated in five environments. For the purpose of increasing the yield of corn grain, breeders should seek to reduce the characters distance from the last node to the first branch of the tassel, tassel length and number of branches. The indirect selection for distance from the last node to the first branch of the tassel would be effective to increase the grain yield. The selection for smaller leaf angle, larger stem diameter and thousand grain weight are favorable for increasing grain yield in maize.